Venice in Films. "Wenecja" by Jan Jakub Kolski (2010) - Grodź, Iwona (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The topic of the article is the image of Venice in Wenecja, a Polish feature film directed by Jan Jakub Kolski from 2010. The imaginary image of this city was inspired by “Sezon w Wenecji” (from the volume titled Jedźmy, wracajmy..., Krakow 1993 or Jedźmy, wracajmy i inne opowiadania, Warsaw 2000), a literary text by Włodzimierz Odojewski (1930–2016). The article undertakes to analyse the image of Venice in the film by the author of Historia kina w Popielawach as a testimony of understanding its role in a particular historical space and time, of both the plot of the film and the projected reception.